EXPLORING THE USE OF WORDWALL GAMES IN LEARNING SPEAKING - Susilawati; Anisa Alawiyyah; Handi Pabriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking anxiety has become a critical issue among elementary school students learning English, as it can significantly hinder their participation and speaking development. Many young learners are reluctant to express themselves orally due to fear of making mistakes, negative evaluation, and low self-confidence, which reduces their opportunities to practice English and develop communicative competence. Therefore, this study aimed to explore the use of Wordwall Games in teaching speaking, examine how Wordwall helps reduce students' speaking anxiety, and investigate students' responses toward its use in speaking activities. This study employed a qualitative approach with a case study design. The research was conducted with third-grade students at Sukamulya Elementary School from March to April 2026. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing or verification to ensure the credibility of the findings. The findings revealed that the implementation of Wordwall Games created an interactive, enjoyable, and supportive learning environment that encouraged students to participate actively in speaking activities. Students became more enthusiastic, confident, and willing to speak English during classroom interactions, and the interactive activities helped them improve their vocabulary, pronunciation, and speaking fluency. Furthermore, Wordwall reduced students' speaking anxiety by creating a more relaxed and comfortable learning atmosphere in which students felt less afraid of making mistakes. Students expressed positive responses toward the use of Wordwall because learning through games increased their motivation, engagement, and confidence in using English for communication.